2018
DOI: 10.3389/fpsyg.2018.00434
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Tones in Mandarin Chinese Infant-Directed Speech: Age-Related Changes in the Second Year of Life

Abstract: Tonal information is essential to early word learning in tone languages. Although numerous studies have investigated the intonational and segmental properties of infant-directed speech (IDS), only a few studies have explored the properties of lexical tones in IDS. These studies mostly focused on the first year of life; thus little is known about how lexical tones in IDS change as children’s vocabulary acquisition accelerates in the second year (Goldfield and Reznick, 1990; Bloom, 2001). The present study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 55 publications
1
18
0
1
Order By: Relevance
“…Vowels in Mandarin Chinese IDS are hyperarticulated (Liu, Tsao, & Kuhl, 2009;Tang, Xu Rattanasone, Yuen, & Demuth, 2017), but vowels in Dutch IDS show hypoarticulation instead (Benders, 2013). In addition, lexical tones in Mandarin Chinese IDS are hyperarticulated (Han, de Jong, & Kager, 2018a;Tang et al, 2017). Related to IDS in word-learning contexts, Johnson, Lahey, Ernestus, and Cutler (2013) showed that, in a word-teaching task, caregivers produced adjectives less frequently compared to common nouns, proper nouns, or verbs.…”
Section: Pitch Properties Of Ids Specific To Word Learning Contextsmentioning
confidence: 95%
“…Vowels in Mandarin Chinese IDS are hyperarticulated (Liu, Tsao, & Kuhl, 2009;Tang, Xu Rattanasone, Yuen, & Demuth, 2017), but vowels in Dutch IDS show hypoarticulation instead (Benders, 2013). In addition, lexical tones in Mandarin Chinese IDS are hyperarticulated (Han, de Jong, & Kager, 2018a;Tang et al, 2017). Related to IDS in word-learning contexts, Johnson, Lahey, Ernestus, and Cutler (2013) showed that, in a word-teaching task, caregivers produced adjectives less frequently compared to common nouns, proper nouns, or verbs.…”
Section: Pitch Properties Of Ids Specific To Word Learning Contextsmentioning
confidence: 95%
“…From infancy through early toddlerhood, the mean length of CDS utterances increases (Stern et al, 1983), the vowel space and individual vowel categories expand and then contract (Bernstein Ratner 1984;Liu et al 2009;Hartman et al 2017, but see Burnham et al 2015;Kalashnikova and Burnham 2018), and speaking rate increases (Ko, 2012;Sjons et al, 2017;Raneri et al, 2020). Fundamental frequency baselines and ranges also change non-linearly throughout this time (Stern et al, 1983;Kitamura et al, 2001;Kitamura and Burnham, 2003;Vosoughi and Roy, 2012;Han et al, 2018). While these studies demonstrate a fairly comprehensive understanding of age-related changes in the acoustics of CDS, our descriptions of phonological-lexical characteristics of CDS, as well as how they change over time, are more superficial.…”
Section: Changes In Child-directed Speech With Agementioning
confidence: 99%
“…Fundamental frequency baselines and ranges also change non-linearly throughout this time (Han, de Jong, & Kager, 2018;Kitamura & Burnham, 2003;Kitamura, Thanavishuth, Burnham, & Luksaneeyanawin, 2001;Stern et al, 1983;Vosoughi & Roy, 2012). While these studies demonstrate a fairly comprehensive understanding of age-related changes in the acoustics of CDS, our descriptions of phonological-lexical characteristics of CDS, as well as how they change over time, are more superficial.…”
Section: Changes In Child-directed Speech With Agementioning
confidence: 96%